Enhanced transdermal delivery of concentrated capsaicin from chili extract-loaded lipid nanoparticles with reduced skin irritation - Phunsuk Anantaworasakul (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. The aim of this study was to develop lipid-based nanoparticles that entrapped a high concentration of capsaicin (0.25%) from a capsicum oleoresin extract. The solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) were strategically fabricated to entrap capsaicin without a hazardous solvent. Optimized nanosize lipid particles with high capsaicin entrapment and loading capacity were achieved from pair-wise comparison of the solid lipid mixtures consisting of fatty esters and fatty alcohols, representing small and large crystal-structure molecules combined with a compatible liquid lipid and surfactants (crystallinity index = 3%). This report was focused on selectively captured capsaicin from oleoresin in amorphous chili extract-loaded NLCs with 85.27% ± 0.12% entrapment efficiency (EE) and 8.53% ± 0.01% loading capacity (LC). The particle size, polydispersity index, and zeta potential of chili extract-loaded NLCs were 148.50 ± 2.94 nm, 0.12 ± 0.03, and −29.58 ± 1.37 mV, respectively. The favorable zero-order kinetics that prolonged capsaicin release and the significantly faster transdermal penetration of the NLC attributed to the reduction in skin irritation of the concentrated capsaicin NLCs, as illustrated by the in vitro EpiDerm™ three-dimensional human skin irritation test and hen’s egg test chorioallantoic membrane assay (HET-CAM).